An Environmentally Friendly Reflectometric Method for Bumetanide Determination in Pharmaceuticals - Pollo, Fernanda [UNESP]; Sequinel, Rodrigo [UNESP]; Rufino, Jose Luiz [UNESP]; Los Weinert, Patricia [UNESP]; Pezza, Helena Redigolo [UNESP]; Pezza, Leonardo [UNESP] (Japan Soc Analytical Chemistry, 2009)
This paper describes a green analytical procedure for the determination of bumetanide using diffuse reflectance spectroscopy. The proposed method is based on reflectance measurements of a violet compound produced from a spot test reaction between bumetanide and p-dimethylaminocinnamaldehyde (p-DAC) in an acid medium, using filter paper as a solid support. The best conditions for the reaction have been found by experimental design methodologies. All reflectance measurements were carried out at 525 nm, and the linear range was from 1.37 x 10(-4) to 1.37 x 10(-3) mol L(-1). with a correlation coefficient of 0.998. The detection limit was estimated to be 3.98 x 10(-5) mol L(-1). Five commercial medicines containing bumetanide were analyzed by the proposed method. No interferences were observed from the common excipients present in pharmaceutical formulations. The results were favorably compared with those obtained by the United States Pharmacopoeia procedure at 95% confidence level.